2008
DOI: 10.1016/j.jvs.2008.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Repair of complex renal artery aneurysms by laparoscopic nephrectomy with ex vivo repair and autotransplantation

Abstract: Repair of complex renal artery aneurysms involving distal branch arteries remains a challenge. This new technique combines the advantages of minimally invasive surgery with the effectiveness of ex vivo aneurysm repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 23 publications
2
56
0
2
Order By: Relevance
“…In their series of seven complex RAA treated by ex vivo repair and autotransplantation, Gallagher et al showed stable renal function postoperatively in all patients. 8 In another study on seven patients Shirodkar et al reported no intraoperative complications and only one case with renal function loss. 9 Recently, Morin et al have described a series of nine patients who underwent ex vivo repair and autotransplantation on solitary kidneys with no detrimental effect on renal function.…”
Section: Discussionmentioning
confidence: 92%
“…In their series of seven complex RAA treated by ex vivo repair and autotransplantation, Gallagher et al showed stable renal function postoperatively in all patients. 8 In another study on seven patients Shirodkar et al reported no intraoperative complications and only one case with renal function loss. 9 Recently, Morin et al have described a series of nine patients who underwent ex vivo repair and autotransplantation on solitary kidneys with no detrimental effect on renal function.…”
Section: Discussionmentioning
confidence: 92%
“…3 Recently, autotransplant after resection of the aneurysm and ex vivo reconstruction of the renal artery have been reported as treatment options with acceptable results. [4][5][6][7] Considering the long operative time from its sequential nature and the potential morbidity it presents, the procedure might be excessive, especially for older patients. In this respect, a kidney transplant to any willing recipient Kidney transplant is the optimal treatment for select patients with end-stage renal disease.…”
Section: Discussionmentioning
confidence: 99%
“…3 Autotransplant, which is performed after nephrectomy, followed by resection of the aneurysm and ex vivo reconstruction of the renal artery, has been reported rarely as a treatment option for patients who require nephrectomy. [4][5][6][7] However, in the era of donor shortages, a kidney transplant to any willing recipient is a treatment option for patients with RAA. We report 2 cases of a renal transplant from donors with RAA, in which hand-assisted laparoscopic nephrectomy, followed by resection of the aneurysm and ex vivo renal artery reconstruction were performed.…”
Section: Introductionmentioning
confidence: 99%
“…5 Other causes for such interventions are symptomatic aneurysms (flank pain, hypertension, hematuria), rapidly expanding aneurysms and those larger than 2 cm. 6 The choice of treatment of RAAs is determined by the anatomic location of the aneurysm. 5 Although stent grafts and stent-plus-coil embolization techniques are successful for most simple RAAs, 7 complex aneurysms beyond the bifurcation of the main renal artery, or those involving major arterial branches, may require extracorporal arterial reconstruction followed by autotransplantation.…”
Section: Introductionmentioning
confidence: 99%
“…5 Although stent grafts and stent-plus-coil embolization techniques are successful for most simple RAAs, 7 complex aneurysms beyond the bifurcation of the main renal artery, or those involving major arterial branches, may require extracorporal arterial reconstruction followed by autotransplantation. 6 …”
Section: Introductionmentioning
confidence: 99%